Evaluating the efficacy of triamcinolone acetonide chewing gum in treating recurrent aphthous stomatitis: A randomized clinical study: Triamcinolone Gum for Recurrent Mouth Ulcers - Bagherzadeh, Saba; Soltanmohammadi, Fatemeh; Rezaee, Haleh; Shahidi, Nikzad; Mahmoudi Gharehbaba, Adel; Javadzadeh, Yousef (Iranian Journal of Pharmaceutical Sciences, 2025)
Recurrent Aphthous Stomatitis (RAS) is a prevalent inflammatory disorder that affects the mouth and is defined by painful ulcers. The precise cause of the condition is still unknown, and the major approach to treatment is mainly centered around managing the symptoms. Triamcinolone acetonide (TA) is a commonly used medication for several conditions. However, due to its potential benefits, there is growing interest in exploring novel drug delivery systems, such as medicated chewing gum (MCG). This study introduces a novel MCG formulation containing TA (T-MCG). We investigated its in vitro drug release and content uniformity before conducting a clinical trial comparing the efficacy of T-MCG versus placebo in patients with RAS. The T-MCG formulation exhibited a sustained release of TA for 120 minutes. The clinical findings demonstrated a notable decrease in the ulcer's size and the mean wound healing period. The results suggest that T-MCG not only improves the effectiveness of TA treatment by releasing the drug over a longer period and allowing it to stay in the mouth longer but also increases patient adherence due to its pleasant composition.